Patterns of breastfeeding practices among children aged one to five years in jaffna district - Kandeepan, K.; Balakumar, S.; Arasaratnam, V. (University of Jaffna, 2012)
Breastfeeding is pivotal to infants and early childhood period to their normal physical and mental growth. Currently, Sri Lanka has adopted the World Health Organization (WHO) recommendation of exclusive breastfeeding for six months, followed with continuation of breastfeeding up to or beyond two years. The objective of this study was to assess the patterns of breastfeeding practices among children aged one to five years in Jaffna district. Multistage cluster sampling was used and 856 children aged one to five years were selected from Jaffna district, proportionate to the population. Among 856, 10 (1.2%) of the children were non-respondents and response rate was 98.8%. Information regarding households including socio-demographic status and breastfeeding patterns were recorded by using pretested and prerecorded interviewer administered questionnaires. Data entry and analysis was done using SPSS Version 16. A total of 846,414 (48.9%) were males. The mean (±SD) age of children was 34.6 (±13.1) months. The median duration of exclusive breastfeeding (EBF) was five months (SD=1.6). In this study population, 64.4% (n=545) children were exclusively breastfed until the completion of 6 months, while 2.6% (n=22) were never exclusively breastfed, and 0.47% (n=4) continued exclusive breastfeeding beyond 6 months. Of the total, 0.4% of mothers were not properly educated and they have stopped EBF before 3.5 months while 9.8%, 85.4%, and 4.5% of mothers were on primary, secondary and tertiary educational level and they have stopped EBF before 4.2, 5.8, and 5.4 months respectively [Pearson's correlation coefficient (0.781) was significant at the 0.05 level]. Of this total population, 261 (30.8%) mothers had been continuing breastfeeding at the time of data collection while 585 (69.1%) of mothers had stopped breastfeeding to their children. Of this 585 children, 55.6% (n=325) of children were breastfed beyond 2 years while 12.6% (n=74) of children were breastfed beyond 3 years. Few number of mothers stopped breastfeeding to their children [7.5% (n=44)] within one year. Of a total of 261 children who were on breastfeeding, 29.9% (n=78) were breastfed beyond two years while 62.4% were on breast feeding within the period between 1-2 years. Based on this research finding, it appears that the rate of exclusive breastfeeding is still lower than national data of Sri Lanka and the duration of breastfeeding in this study population has not reached 2 years of satisfactory period.
Keywords: Exclusive breastfeeding; Feeding pattern; Pearson’s correlation; Multistage cluster sampling